EFFECT OF OPTIC DISK—FOVEA DISTANCE ON MEASUREMENTS OF INDIVIDUAL MACULAR INTRARETINAL LAYERS IN NORMAL SUBJECTS. Issue 5 (May 2019) - Qiu, Kunliang; Chen, Binyao; Chen, Haoyu; Gao, Enting; Yang, Jianling; Chen, Xinjian; Zhang, Mingzhi
Abstract : Purpose: To investigate the effect of optic disk—fovea distance (DFD) on measurements of macular intraretinal layers using spectral domain optical coherence tomography in normal subjects. Methods: One hundred and eighty-two eyes from 182 normal subjects were imaged using spectral domain optical coherence tomography. The average thicknesses of eight macular intraretinal layers were measured using an automatic segmentation algorithm. Partial correlation test and multiple regression analysis were used to determine the effect of DFD on thicknesses of intraretinal layers. Results: Disk—fovea distance correlated negatively with the overall average thickness in all the intraretinal layers (r ⩽ −0.17, all P ⩽ 0.025) except the ganglion cell layer and photoreceptor. In multiple regression analysis, greater DFD was associated with thinner nerve fiber layer (6.78 μ m decrease per each millimeter increase in DFD, P < 0.001), thinner ganglion cell—inner plexiform layer (2.16 μ m decrease per each millimeter increase in DFD, P = 0.039), thinner ganglion cell complex (8.94 μ m decrease per each millimeter increase in DFD, P < 0.001), thinner central macular thickness (18.16 μ m decrease per each millimeter increase in DFD, P < 0.001), and thinner total macular thickness (15.94 μ m decrease per each millimeter increase in DFD, P < 0.001). Conclusion: Thinner measurements of macular intraretinal layers were significantly associated with greater DFD. A clinical assessment of macular intraretinal layers in the evaluation of various macular diseases should always be interpreted in the context of DFD. Abstract : Thinner measurements of macular intraretinal layers were significantly associated with greater optic disk—fovea distance. A clinical assessment of thickness measurements of macular intraretinal layers in the evaluation of various retina diseases involving macular changes should take into consideration of optic disk—fovea distance.